Efektifitas Aplikasi PSDS (Pegadaian Syariah Digital Service) Dalam Meningkatkan Jumlah Nasabah - Feni Hariyati; Fathuddin Abdi; Mellya Embun Baining (Indonesian Journal of Islamic Economics and Business, 2020)
This paper aims to reveal the effectiveness of online services carried out by Jelutung Syariah Pegadaian through the Mobile application of Pegadaian Syariah Digital Services (PSDS) in increasing the number of customers. This descriptive qualitative data collection method through observation, interviews, and documentation. Based on the research results, the effectiveness of PSDS services is reviewed through 7 dimensions, namely efficiency, reliability, fulfillment, privacy, responsiveness, compensation, and contact. Of the seven dimensions, there are 3 dimensions that have not been maximally achieved, namely efficiency, reliability, and responsiveness. Meanwhile, to achieve this effectiveness, it is reviewed from the implementation of its management function which consists of planning, organizing, actuating, controlling. Which has been going well under the direct leadership of the head of the Jelutung Sharia Pegadaian branch. Then regarding the increase in the number of customers that occurred, it was not that many but had met expectations, namely targeting customers at a young age or millennials.